Estimation of the Early Cs-137 Intake of Evacuees from Areas Affected by the 2011 Fukushima Daiichi Nuclear Power Plant Accident Based on Personal Behavioral Data and the Latest Atmospheric Transport and Dispersion Model Simulation. Issue 2 (August 2021) - Kim, Eunjoo; Igarashi, Yu; Hashimoto, Shozo; Tani, Kotaro; Ishikawa, Tetsuo; Kowatari, Munehiko; Kurihara, Osamu
Abstract : Abstract: More than 9 y have passed since the 2011 nuclear disaster in Fukushima Prefecture, Japan. During this period, much effort has been spent on the dose reconstruction for Fukushima residents; however, the estimation of the internal dose due to the potential intake of the short-lived radionuclides (mainly iodine-131) has been challenging because of the lack of direct human measurements at the early phase of the accident. Our previous study revealed that the residual cesium body contents observed in delayed whole-body counter (WBC) measurements of residents from Namie-town, one of the most affected municipalities, varied greatly with the timepoint of their evacuations on 12 March 2011 when the first explosive event occurred at the accident site; i.e., the late evacuees had much higher residual cesium body contents compared to the prompt evacuees. The present study thus aimed to clarify this finding by reproducing the exposure situation based on the evacuees' personal behavioral data in combination with the latest atmospheric transport and dispersion model (ATDM) simulation for 356 selected subjects in adult and 15-y (13–17 y) age groups. The results demonstrated that the ATDM simulation-based method could reasonably reproduce the subjects' exposure situation, supporting the previous finding. However, the residual cesium-137 body contents calculated by this method were only 10%–20% of those in the subjects' WBC measurements. This large discrepancy was considered to be caused by both the present method's underestimation and the overestimation of the subjects' early intake in the WBC measurements due to a conservative intake scenario not assuming potential additional intake. Additional studies are needed to further clarify the reasons for the discrepancy and to evaluate the magnitude of the inhalation dose in the accident. Abstract : Supplemental digital content is available in the text.